Duchenne Muscular Dystrophy - Family in a Crisis - Amin, M Robed; Borua, Chowdhury Chironjib; Alam, Kaji Shafiqul; Chowdhury, Fazle Rabbi; Sarkar, Rabiul Jahan; Khandaker, Md Abul Kashem; Faiz, MA (Journal of Medicine, 2009)
Progressive muscular weakness with deformity leading to crippled states develop due to musculoskeletal and neurological disorders. Sometimes it is difficult to differentiate between primary muscle disease and neurological disease. But there is some classical presentation of muscle diseases which have its own entity and thus can be clinically differentiated from neurological disorder especially spinal cord and motor neuron diseases. Muscular dystrophy is one of those disorder with distinct clinical features. Muscular dystrophy refers to a group of genetic, hereditary muscle diseases that cause progressive muscle weakness. Most types of MD are multi-system disorders with manifestations in body systems including skeletal system, the heart, gastrointestinal and nervous systems, endocrine glands, skin, eyes and other organs. Duchenne muscular dystrophy (DMD), is inherited in an X-linked recessive pattern, meaning that the mutated gene that causes the disorder is located on the X chromosome, one of the two sex chromosomes, and is thus considered sex-linked. Males are therefore affected by X-linked recessive disorders much more often than females. A characteristic of X-linked inheritance is that fathers cannot pass X-linked traits to their sons. Duchenne muscular dystrophy and Backers muscular dystrophy are caused by mutations of the gene for the dystrophin protein and lead to an overabundance of the enzyme creatine kinase. The dystrophin gene is the largest gene in humans. In this case series a family with three brothers suffering from Duchenne muscular dystrophy is described and review with literature was done. Â doi:10.3329/jom.v10i3.2015 J Medicine 2009; 10 (Supplement 1): 36-39